2015
DOI: 10.1016/j.jhep.2014.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Partial hepatectomy vs. transcatheter arterial chemoembolization for resectable multiple hepatocellular carcinoma beyond Milan criteria: A RCT

Abstract: We would like to emphasize the importance of actively searching for infections, even if not clinically evident, in any cirrhotic patient with cognitive impairment. Conflict of interestThe authors declared that they do not have anything to disclose regarding funding or conflict of interest with respect to this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Previous studies have reported that PLT-based models can be used to predict patient survival (15,(29)(30)(31). Similar to the present study, Qin et al (66) demonstrated that FIB-4 >3.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported that PLT-based models can be used to predict patient survival (15,(29)(30)(31). Similar to the present study, Qin et al (66) demonstrated that FIB-4 >3.…”
Section: Discussionsupporting
confidence: 89%
“…Although recent studies have demonstrated that abnormal PLT counts are associated with a poor prognosis in patients with cancer, this association remains controversial (27,28). In addition, previous studies have reported a correlation between PLT-based models and the recurrence and overall survival rate in patients with malignant hepatic tumors (15,(29)(30)(31)(32). In the present study, 18 PLT-based models were used to predict the overall survival and recurrence-free survival in patients with malignant hepatic tumors.…”
Section: Introductionmentioning
confidence: 86%
“…Although transarterial chemoembolization (TACE) is recommended as the standard treatment for BCLC‐B HCC, various other treatments including liver resection have been used in clinical settings. Recent studies have provided evidence supporting the survival benefit of resection for BCLC‐B HCC, but the issue remains controversial. Well designed studies comparing liver resection with non‐surgical treatments such as TACE are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…, TACE). However, for tumors confined to the same segment or the ipsilateral half of the liver, surgical resection may achieve better outcomes than other treatment modalities[ 6 , 7 ]. In the present case, as the tumor was not only located in the right lobe but also in the left medial lobe (Figure 5A ), an anatomical right trisectionectomy was required.…”
Section: Discussionmentioning
confidence: 99%